2013
DOI: 10.1016/j.jbiotec.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of inhibitors of yeast-to-hyphae transition in Candida albicans by a reporter screening assay

Abstract: Candida albicans is one of the most common opportunistic fungal pathogens, causing lifethreatening disease in immunocompromised patients. As it is not primarily a pathogen, but can exist in a commensal state, we aimed at the identification of new anti-infective compounds which do not eradicate the fungus, but primarily disable a virulence determinant. The yeast-hyphae-dimorphism of C. albicans is considered a major contributor to fungal disease, as mutants locked into either yeast or hyphal state have been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
1
17
0
1
Order By: Relevance
“…The role of Tup1 in fungal dimorphism might well be linked to nitrogen metabolism as nitrogen availability has been shown to be an important factor in fungal dimorphism [84][88]. We suggest that the link to nitrogen metabolism and TupA is important to understand the involvement of TupA in developmental processes and dimorphic switches in fungi.…”
Section: Discussionmentioning
confidence: 86%
“…The role of Tup1 in fungal dimorphism might well be linked to nitrogen metabolism as nitrogen availability has been shown to be an important factor in fungal dimorphism [84][88]. We suggest that the link to nitrogen metabolism and TupA is important to understand the involvement of TupA in developmental processes and dimorphic switches in fungi.…”
Section: Discussionmentioning
confidence: 86%
“…A representative of antraquinones – purpurin – supresses hyphal growth at the concentration of 3 μg/mL (Tsang et al ., ), whereas emodin causes the same effect at about 2.5‐fold lower concentration (Figure d). High‐throughput screening performed by Heintz–Bushart and others revealed that compounds from methyl aryl‐oxazoline carboxylate, dihydrobenzo[d]isoxazolone and thiazolo[4,5‐e]benzoisoxazole families can effectively suppress hyphal production (Heintz‐Buschart et al ., ). Messier and coworkers found that natural isopentenyloxychalcone, 4‐hydroxycordoin, inhibits hyphal formation of C. albicans at a concentration ranging from 50 to 200 μg/mL (Messier et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Hence, in order to facilitate better control of morphology switch CONTACT Ri Ming Yan rimingyan@163.com; yanriming@jxnu.edu.cn; Du Zhu zhudu12@163.com *Both authors contributed equally to this work and further understanding of the dimorphic transitions mechanisms, a great number of investigations into the nutritional and environmental stimuli which can induce dimorphic transitions have been conducted. Previous investigations have documented that dimorphic transition is normally induced by a variety of environmental and nutritional factors including temperature [9], quorum sensing molecules [5], inoculum size [16], the accessibility of nitrogen source [14] and carbon [17], the concentration of serum [7], amino acid [18], pH [19] and so on. Despite many different environmental factors that can induce dimorphism transition, the signalling pathways involved in connecting external stimuli and cell morphological transformation are highly conserved even among distantly related fungi [14,20].…”
Section: Introductionmentioning
confidence: 99%